No Evidence for the Involvement of Leiomodin-1 Antibodies in the Pathogenesis of Onchocerciasis-Associated Epilepsy - Hotterbeekx, An (Pathogens, 2021)
Nodding syndrome has been suggested to be triggered by neurotoxic leiomodin-1 auto-antibodies cross-reacting with Onchocerca volvulus. Here, we screened serum and CSF samples of persons with nodding syndrome and other forms of onchocerciasis-associated epilepsy (OAE) and African and European controls for leiomodin-1 antibodies by a cell-based assay (CBA) and Western blot (WB). These samples were also investigated for the presence of auto-antibodies cross-reacting with rat brain tissue by immunohistochemistry (IHC). Additionally, IHC was used to detect the leiomodin-1 protein in post-mortem brain samples of persons with OAE who died. Leiomodin-1 antibodies were detected by CBA in 6/52 (12%) and by WB in 23/54 (43%) persons with OAE compared to in 14/61 (23%) (p = 0.113) and 23/54 (43%) (p = 0.479) of controls without epilepsy. Multivariable exact logistic regression did not show an association between O. volvulus infection or epilepsy status and the presence of leiomodin-1. Leiomodin-1 antibodies were not detected in 12 CSF samples from persons with OAE or in 16 CSF samples from persons with acute-onset neurological conditions, as well as not being detected in serum from European controls. Moreover, the leiomodin-1 protein was only detected in capillary walls in post-mortem brain tissues and not in brain cells. IHC on rat brain slides with serum samples from persons with OAE or controls from persons with or without O. volvulus infection revealed no specific staining pattern. In conclusion, our data do not support OAE to be an autoimmune disorder caused by leiomodin-1 antibodies.